Jump ability and force-velocity profile in rhytmic gymnastics - Ferreira Melo de Sá, L.; Leite, I.; Batista Santos, A.; Tristão Ávila Carvalho, M. de L. (Science of Gymnastics Journal, 2023)
The jump is one of the main body elements in Rhythmic Gymnastics (RG). To perform it correctly, gymnasts must develop appropriate force and velocity levels to reach enough jump height to show the body shape during flight, as defined by the RG Code of Points. Jumping performance is influenced by the mechanical force-velocity (F-V) profile and the maximum power generated by the lower limbs. The F-V profile identification can provide a more accurate and complete mechanical representation of its capabilities and needs. This study aimed to analyse the F-V profile during the counter movement jump of RG athletes, identify the magnitude and direction of the imbalance between the two variables (force and velocity), and compare the jumping ability and mechanical variables of different age groups. Eighteen Portuguese gymnasts (average age 12.2±1.8 years) were evaluated, according to age group: beginner and youth gymnasts (G1- ages 10 to 12) and junior and senior gymnasts (G2 - ages 13 to 16), and according to the F-V profile imbalance detected. The data collection was performed after a covid-19 lockdown period. Results showed anthropometric differences between age groups but no differences in the F-V profile related variables. When gymnasts were compared according to the deficit, differences were found in variables force and velocity. Furthermore, 72.3% of the gymnasts presented force deficit, 11% presented velocity deficit and 16.6% were balanced. Considering the deficits found, the demands of the sport and of each athlete, it is essential to include strength training in the regular training routines of rhythmic gymnasts.